Analysis of CD31 expression and vascular parameters in human placentas from pregnant women with intrauterine growth restriction - Vesna Ljubojević; Sanja Jovičić; Dragica Draganović; Ljiljana Amidžić; Biljana Vatreš; Nataša Vojinović (Биомедицинска истраживања, 2022)
Introduction: Placental dysfunction is underlying cause in most of the intrauterine growth restriction and the pregnancy complications where the fetus does not achieve its genetically determined potential for growth. The critical process for the development of the placenta is angiogenesis. CD31 is an important endothelial adhesion protein that enables angiogenesis. The study aimed to analyze the CD31 expression and vascular parameters in normal placentas and IUGR placentas. Methods: Thirty placental samples, fifteen IUGR placentas, and fifteen term normal placental samples were analyzed. The hematoxylin-eosin method and immunohistochemical method with anti CD31 antibody were used for the staining of the tissue sections. The analyzed vascular parameters were: capillary number density (CND), capillary area density (CAD), and capillary surface density (CSD). Results: Between normal placentas and IUGR placentas there was no determined difference in CD31 expression. Positive intensive staining of CD31 was found in the endothelium of all blood vessels and no staining was observed in cytotrophoblast and syncytiotrophoblast cells. In IUGR placentas, CND of 2.55 capillary/1000 µm2 villous area was significantly decreased compared to normal placentas of 3.49 capillary/1000 µm2 villous area. CAD in IUGR placentas of 30.49 % was significantly decreased compared to normal placentas of 52.80 % villous area. CSD in IUGR placentas (92.81 µm/1000µm2) was significantly reduced compared to CSD in normal placentas (145.51 µm/1000µm2). Conclusion: The localization and intensity of CD31 expression were not different between the IUGR and normal placentas. Histological vascular parameters of placental villi are decreased in the IUGR placenta. In case of intrauterine growth restriction, there is a reduced vascularization of the terminal villi of the placenta.
Keywords: placenta; intrauterine growth restriction; CD31 expression; vasculature